Learning from high-attending urban Indigenous students: a case study - Baxter, Lindy; Meyers, Noel (The Australian Journal of Indigenous Education, 2020)
Abstract This project focused on 45 Indigenous students who attended most often (90–100%) at an Australian urban primary school to identify factors that facilitate high attendance. We analysed student records and to provide student voice, an Indigenous Worker in the school conducted a student questionnaire. Student responses showed friendships, relationships, family stability and resilience were important contributors for high attendance. Administrative data revealed poverty was the only almost universally shared trait. Common characteristics among students were identified at cohort-level. At student-level, no combination or single trait applied to every high-attending student. They showed great diversity. The study school's attendance strategies included increasing cultural inclusion and support for students living in poverty, which positively impacted many students' attendance, although not all. A personalised approach was also required. An Indigenous Worker identified individual student's attendance barriers and tailored solutions. If school-level strategies are ineffective for all students, strategies and policies designed for all of Australia's Indigenous students will also affect only some of the population. Without a personalised approach, Closing the Gap attendance strategies were limited in reach, and ultimately success. Refreshing the Closing the Gap strategy now provides opportunities for attendance strategies to include personalised approaches.